Laceration and degloving injury of a child's foot--a case report - Cáp, R; Lochman, P; Horyna, P; Koudelka, J; Klein, L (Acta chirurgiae plasticae, 2009)
Laceration and degloving injury to a child's foot is quite a rare occurence, mostly resulting in persistent consequences. Treatment options for such an injury depend on the specific type of injury and the customary practice of each surgical department. The authors present the interesting case of 4-year-old boy with laceration and degloving injury to his right foot after a collision with a truck, suggesting simple treatment using skin graft which has an excellent functional and cosmetic effect. Several methods have been described in management of this kind of injury, such as microvascular free tissue transfer, free or local flap and skin graft. A full-thickness skin graft was used in this case with good result, and in our opinion this treatment option need not be reserved for plastic surgeons.
Keywords: Lacerations; mužské pohlaví; Male; Humans; dopravní nehody; lacerace; následné studie; lidé; hojení ran; Follow-Up Studies; Trauma Severity Indices; ukazatel závažnosti úrazu; transplantace kůže; Wound Healing; poranění nohy (od hlezna dolů); chirurgické laloky; Foot Injuries; Surgical Flaps; Accidents, Traffic; Child, Preschool; Skin Transplantation; předškolní dítě